2018
DOI: 10.1007/s10726-018-9559-9
|View full text |Cite
|
Sign up to set email alerts
|

Why so Serious? Theorising Playful Model-Driven Group Decision Support with Situated Affectivity

Abstract: An integrative approach to theorising behavioural, affective and cognitive processes in model-driven group decision support (GDS) interventions is needed to gain insight into the (micro-)processes by which outcomes are accomplished. This paper proposes that the theoretical lens of situated affectivity, grounded in recent extensions of scaffolded mind models, is suitable to understand the performativity of affective micro-processes in model-driven GDS interventions. An illustrative vignette of a humorous micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 100 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…Ackermann et al (2016) used a group support system to address conflicts between two organizations. Group support systems (Ackermann et al , 2005; Eden, 1992; George et al , 1992; Burger et al , 2018) help observe specific group dynamics and thus can identify the network condition by which team EI emerges in each team.…”
Section: Discussionmentioning
confidence: 99%
“…Ackermann et al (2016) used a group support system to address conflicts between two organizations. Group support systems (Ackermann et al , 2005; Eden, 1992; George et al , 1992; Burger et al , 2018) help observe specific group dynamics and thus can identify the network condition by which team EI emerges in each team.…”
Section: Discussionmentioning
confidence: 99%
“…Video recording was used to create a rich record of the participant interactions insitu (Lipshitz, Klein, Orasanu, & Salas, 2001), in addition to the author being present at the workshop. This is a suitable approach for capturing the micro-behaviours of the participants during the problem structuring activities (Baker, Bunch, & Kelsey, 2015;Burger et al, 2018;Burger, White, & Yearworth, 2019;Crowe et al, 2011;Paroutis, Franco, & Papadopoulos, 2015;White, Burger, & Yearworth, 2016). When video recording is used as a data collection instrument, questions arise around possible participant reactivity to the research instrument affecting the natural course of interactions as a result of being observed (Lomax & Casey, 1998;Paterson, 1994).…”
Section: Data Collectionmentioning
confidence: 99%
“…Specifically, considering participant engagement in-situ, experienced OR practitioners suggest that models "can be toys that a group can play with together" (Eden, 1992a), that participant engagement in problem structuring interventions is brought about in the process of "doing what feels good" (White & Taket, 1993) and that "creating and sustaining connections within systems that are uplifting, open, and mutually beneficial" (Hämäläinen, Jones, & Saarinen, 2014, p. 103) is important for engagement. Yet, to date, few studies have attempted to make the micro-processes (Ackermann, Yearworth, & White, 2018;Franco & Greiffenhagen, 2018) of such participant experiences in-situ visible and thereby accessible for reflection (Ackermann, Eden, & Pyrko, 2016;Burger, White, & Yearworth, 2018). As such, there is a lack of a conceptual repertoire to assist OR practitioners with understanding how such situated motivational engagement of participants in problem structuring interventions unfolds.…”
Section: Introductionmentioning
confidence: 99%
“…The use of narrative vignettes in the literature on group decision-making to identify micro-processes was exemplified by Burger et al (2018). They used a vignette to illustrate the micro-processes at play in a group decision workshop.…”
Section: Vignettes To Explore Narrativementioning
confidence: 99%
“…Each of these activities represents a succession of goal-driven cognitive and social micro-processes. The study of micro-processes involves "understanding how interaction is coordinated in ways that help to create shared understanding with a particular focus on shared symbolic systems among the participants in situ" (Burger et al 2018). At the same time, decision performance is dynamic and time dependent (Brehmer 1992).…”
mentioning
confidence: 99%